Methotrexate-loaded sulfonated bacterial cellulose / chitosan hydrogel for treating psoriasis and preparation method of methotrexate-loaded sulfonated bacterial cellulose / chitosan hydrogel
By sulfonated bacterial cellulose/chitosan hydrogel loading methotrexate, the problem of poor skin treatment and major side effects in the prior art is solved, and efficient and safe treatment of psoriasis is achieved .
Patent Information
- Application Number
- CN202411343733.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-10
AI Technical Summary
The existing treatment methods for psoriasis have problems with great side effects and poor efficacy, especially the hydrophobicity and cell bioavailability of methotrexate, which leads to poor skin treatment, and the microneedle structure may lead to the skin. damage.
Using sulfonated bacterial cellulose/chitosan hydrogel as methotrexate carrier, the complexation of sulfonated bacterial cellulose and chitosan to form a stable hydrogel, which enhances the skin bioadhesion of the drug and biological biologicity of the drug. Compatibility to achieve sustained release of methotrexate and precise transdermal administration.
It improves the skin permeability and sustained release properties of methotrexate, reduces side effects, significantly improves the therapeutic effect of psoriasis, and has good biocompatibility and safety.
Smart Images

Figure CN119280140A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomedical materials and relates to a sulfonated bacterial cellulose / chitosan hydrogel loaded with methotrexate for treating psoriasis and a preparation method thereof. Background Art
[0002] Psoriasis is a chronic, systemic, immune-mediated disease characterized by excessive proliferation of keratinocytes and infiltrating immune cells. In addition to affecting the skin, nails and joints, more and more studies have shown that patients with psoriasis have an increased risk of cardiovascular disease, metabolic syndrome, inflammatory bowel disease and chronic kidney disease. The pathogenesis of psoriasis is not fully understood and may involve multiple aspects such as genetics, environment and immune system. Injury, infection or mechanical stimulation can cause abnormal proliferation and differentiation of keratinocytes and infiltration of inflammatory cells in psoriasis. Currently, commonly used systemic drugs for the treatment of psoriasis include retinoids, methotrexate (MTX), cyclosporine and new immunosuppressants including anti-TNFα antibodies, IL12 / 23 antibodies, IL17A antibodies, IL23p19 antibodies, etc. However, due to the different side effects of the above treatment methods and the relative singleness of the target link, their therapeutic effects and application prospects are not yet completely satisfactory, and systemic medication is often accompanied by serious side effects, such as gastrointestinal toxicity, liver damage, bone marrow suppression, and infection caused by low immunity. Therefore, local transdermal drug delivery has been a research hotspot for the treatment of psoriasis in recent years. Improving the permeability of transdermal drug delivery and promoting drug breakthrough through the stratum corneum are important means to improve the efficacy of transdermal drug delivery.
[0003] MTX is one of the most effective traditional drugs for the treatment of psoriasis. It is a cytotoxic drug with anti-inflammatory, antiproliferative and immunomodulatory effects. The clinical efficacy of MTX is dose-related, but increasing the dose of MTX also poses the risk of causing greater side effects. The main reason for clinical discontinuation of MTX is not the lack of effectiveness but the adverse reactions it causes, such as gastrointestinal toxicity, bone marrow transplantation and hepato-renal toxicity; due to its hydrophobicity and cellular bioavailability, MTX is currently routinely used in the form of oral tablets and injections. Therefore, the use of hydrogel-loaded methotrexate for transdermal delivery targeting psoriasis is a reasonable research direction, providing novel ideas and opportunities for the treatment of psoriasis.
[0004] Hydrogels have become promising topical drug delivery vehicles due to their unique properties, such as easy application and ability to form a protective barrier on the skin. Currently, there are few studies on methotrexate-loaded hydrogels for the treatment of psoriasis. Zhao P et al. and Dai P et al. respectively prepared microneedle hydrogels loaded with methotrexate for the treatment of psoriasis (Zhao P, Li Z, Ling Z, Zheng Y, et al. Efficient Loading and Sustained Delivery of Methotrexate Using a Tip-Swellable Microneedle Array Patch for Psoriasis Treatment. ACS Biomater Sci Eng. 2024; 10(2): 921-931. doi: 10.1021 / acsbiomaterials.3c01810; Dai P, Ge X, Sun C, et al. A Novel Methacryloyl Chitosan Hydrogel Microneedles Patch with Sustainable Drug Release Property for Effective Treatment of Psoriasis. Macromol Biosci.2023;23(12):e2300194.doi:10.1002 / mabi.202300194), but the microneedle structure still has the risk of causing skin damage, especially in psoriasis, where trauma may lead to the occurrence of isomorphic reactions. Therefore, it is still necessary to explore other hydrogel systems suitable for loading methotrexate to meet the needs of local treatment of psoriasis.
[0005] Cellulose and chitosan-based biocomposites have emerged as renewable materials for wound management and drug delivery (StrnadS, Cellulose-Chitosan Functional Biocomposites. Polymers (Basel). 2023; 15(2): 425. Published 2023Jan 13. doi: 10.3390 / polym15020425). However, the highly porous structure of bacterial cellulose cannot resist the free movement of small molecules, so it needs to be modified to expand its application in the field of drug delivery. Summary of the invention
[0006] The object of the present invention is to provide a sulfonated bacterial cellulose (SBC) / chitosan (CS) hydrogel loaded with methotrexate for the treatment of psoriasis and a preparation method thereof. The sulfated bacterial cellulose / chitosan composite hydrogel of the present invention has the ability to encapsulate and maintain the release of methotrexate, and has good skin bioadhesion and biocompatibility, and can be used as a carrier for transdermal drug delivery.
[0007] The technical solution to achieve the purpose of the present invention is:
[0008] The preparation method of the sulfonated bacterial cellulose / chitosan hydrogel loaded with methotrexate for treating psoriasis comprises the following steps:
[0009] Step 1, dissolving bacterial cellulose and aminosulfonic acid in N,N-dimethylformamide (DMF), reacting in a closed container at 50±10° C. for 2 to 12 hours, adding anhydrous ethanol to terminate the reaction, adjusting the pH to 7 to 8, dialyzing, washing, centrifuging and homogenizing to obtain a sulfonated bacterial cellulose suspension;
[0010] Step 2, mixing methotrexate with the sulfonated bacterial cellulose suspension, stirring evenly, to obtain a methotrexate-loaded sulfonated bacterial cellulose (MTX-SBC) suspension;
[0011] Step 3, according to the mass ratio of chitosan to sulfonated bacterial cellulose of 1:4 to 1:1, the sulfonated bacterial cellulose suspension loaded with methotrexate and the acetic acid solution of chitosan are mixed, stirred evenly, and allowed to stand to solidify to obtain a sulfonated bacterial cellulose / chitosan (MTX-SBC / CS) hydrogel loaded with methotrexate.
[0012] Preferably, in step 1, the mass ratio of bacterial cellulose to aminosulfonic acid is 2:7.5.
[0013] Preferably, in step 1, the reaction time is 4 to 8 hours.
[0014] Preferably, in step 1, the concentration of sulfonated bacterial cellulose in the sulfonated bacterial cellulose suspension is 0.04 g / ml.
[0015] Preferably, in step 1, the molecular weight of the dialysis bag used for dialysis is 8000-14000, and the dialysis time is 5-7 days.
[0016] Preferably, in step 2, the mass ratio of methotrexate to sulfonated bacterial cellulose is 1:4, and the concentration of methotrexate in the sulfonated bacterial cellulose suspension loaded with methotrexate is 1 mg / ml.
[0017] Preferably, in step 2, the stirring method is magnetic stirring, the stirring time is 30 min, and the rotation speed is 100 rpm.
[0018] Preferably, in step 3, the acetic acid solution of chitosan is prepared by dissolving chitosan in a 2% (w / v) acetic acid solution, and the concentration of chitosan is 1-2% (w / v).
[0019] Preferably, in step 3, the mass ratio of chitosan to sulfonated bacterial cellulose is 1:2.
[0020] Preferably, in step 3, the standing temperature is room temperature and the standing time is 12 hours.
[0021] The invention also provides the methotrexate-loaded sulfonated bacterial cellulose / chitosan hydrogel prepared by the preparation method.
[0022] Furthermore, the present invention provides the use of the above-mentioned sulfonated bacterial cellulose / chitosan hydrogel loaded with methotrexate in the preparation of a drug for treating psoriasis.
[0023] Compared with the prior art, the present invention has the following advantages:
[0024] (1) The present invention utilizes negatively charged sulfate to sulfonate bacterial cellulose, and the obtained negatively charged bacterial cellulose interacts with chitosan carrying active amino groups and positive charges to form a stable composite hydrogel material system. The sulfonated bacterial cellulose further enhances the hydrophilicity and biocompatibility of the composite material, which is beneficial to the transmembrane absorption of MTX.
[0025] (2) The synthesis method of the present invention is simple, and the prepared sulfonated bacterial cellulose / chitosan hydrogel loaded with methotrexate has skin adhesion, can encapsulate hydrophobic drugs such as MTX by forming hydrogen bonds, and has enhanced solubility and sustained release properties, can adjust drug release under different pH conditions, increase the residence time of methotrexate in psoriasis lesions, and facilitate accurate transdermal administration and drug release. The hydrogel has good biocompatibility and shows excellent therapeutic effect on psoriasis in an IMQ-induced psoriasis-like dermatitis mouse model. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the preparation process of sulfonated bacterial cellulose / chitosan hydrogel loaded with methotrexate.
[0027] Figure 2 Molecular dynamics simulation diagram of MTX adsorption on BC and SBC.
[0028] Figure 3 Scanning electron micrographs of SBC, SBC / CS hydrogel, and MTX-SBC / CS hydrogel.
[0029] Figure 4These are the FTIR detection images of SBC, CS, MTX, SBC / CS hydrogel, and MTX-SBC / CS hydrogel.
[0030] Figure 5 This is the skin adhesion test result of MTX-SBC / CS hydrogel.
[0031] Figure 6 This is the biocompatibility test result of MTX-SBC / CS hydrogel.
[0032] Figure 7 The solubility of MTX in CS, SBC and PBS and the cumulative release curve of MTX from MTX-SBC / CS hydrogel in vitro.
[0033] Figure 8 Results of in vitro skin permeation studies.
[0034] Fig. 9 The results of the mouse experiment to verify the efficacy of MTX-SBC / CS hydrogel; (A) animal experiment flow chart; (B) psoriasis-like images of the back skin of mouse models in different treatment groups; (C) PASI total scores of the back skin of mouse models in different treatment groups.
[0035] Fig.10 H&E staining images of the back skin of mouse models in different treatment groups and qRT-PCR detection of mRNA expression levels of inflammatory factors in the back skin of mouse models in different treatment groups. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with specific embodiments and drawings.
[0037] In the following examples, the synthesis of sulfonated bacterial cellulose was prepared according to the literature (LiX, DingW, WangS, et al. Three-Dimensional Sulfated Bacterial Cellulose / Gelatin Composite Scaffolds for Culturing Hepatocytes. Cyborg Bionic Syst. 2023; 4: 0021. Published 2023Apr12. doi: 10.34133 / cbsystems.0021), and the concentration of the sulfonated bacterial cellulose suspension was 0.04 g / ml.
[0038] Example 1
[0039] 1. Synthesis of Hydrogel
[0040] (1) Synthesis of MTX-SBC / CS hydrogel
[0041] 10 ml of sulfonated bacterial cellulose suspension was mixed with 10 mg of MTX and stirred magnetically for 30 minutes to form an MTX-SBC suspension with an MTX concentration of 1 mg / ml. 1 g of chitosan was dissolved in 50 ml of 2% acetic acid solution to prepare a 2% chitosan acetic acid solution. 10 ml of 2% chitosan acetic acid solution was added to the MTX-SBC suspension and allowed to stand at room temperature for 12 hours to prepare an MTX-SBC / CS hydrogel.
[0042] (2) Synthesis of SBC / CS hydrogel
[0043] The synthesis method of SBC / CS hydrogel is roughly the same as that of MTX-SBC / CS hydrogel, except that MTX is not added.
[0044] 2. Characterization and detection
[0045] Scanning electron microscopy (SEM) was used for microstructure detection. Fourier transform infrared spectroscopy (FTIR)-20c was used for analysis with a scanning range of 500-4000 cm -1 , resolution 4cm -1 .
[0046] 3. Skin adhesion test
[0047] Fresh pig skin was cut into 10 mm × 30 mm slices, soaked in PBS for 24 h, and then the two surfaces were bonded with MTX-SBC / CS hydrogels with an area of 10 mm × 10 mm at room temperature. After 1 h, the sample was -1 The adhesion strength was calculated as the load force per bonding area.
[0048] 4. Biocompatibility testing
[0049] C57BL / 6 mice were randomly divided into 4 groups (n=5 in each group), including a blank control group, a positive control group for irritant dermatitis treated with 1% 2,4-dinitrochlorobenzene (DNCB), and an experimental group that applied 1 ml of SBC / CS hydrogel or MTX-SBC / CS hydrogel to the back skin every day for six consecutive days. The skin reactions of the mice were monitored daily before and after the application of the hydrogel throughout the experiment. Histopathological examination of the dorsal skin was performed to confirm the observed skin irritation.
[0050] 5. Solubility and in vitro drug release test
[0051] Excess MTX was added to 1 mL of PBS, 2% chitosan in acetic acid, and sulfonated bacterial cellulose suspensions to determine the maximum solubility of MTX in each solvent. The solubility was obtained by observing the saturation point of each system, where MTX did not dissolve further, indicating its solubility limit.
[0052] In vitro release studies were performed using a modified dialysis method, and 3 ml of MTX-SBC / CS hydrogel with a MTX concentration of 0.5 mg / mL was placed in a 14,000 Da dialysis bag. The bag was sealed and immersed in 300 mL of PBS solution (pH 5.5 or 7.4) and continuously shaken at 37°C and 100 rpm. The control group consisted of 3 mL of 0.5 mg / mL MTX solution in PBS. At specified time intervals (0, 0.5, 1, 2, 4, 8, 12, and 24 hours), 3 mL of samples were collected. The collected samples were analyzed at 302 nm using a UV-visible spectrophotometer.
[0053] 6. Skin permeability study
[0054] In the transdermal effect of SBC / CS hydrogel, fluorescein isothiocyanate (FITC) was used as a tracer, and mouse skin was treated with FITC-SBC / CS gel (containing 0.5 mg / mL FITC, used in 1 mL) and FITC-PBS solution (also containing 0.5 mg / mL FITC, used in 1 mL) for 24 hours. After treatment, the skin tissue was excised and directly frozen and sectioned, and the transdermal effect of these sections was observed under a fluorescence microscope. To evaluate the penetration of MTX, pig skin was cut into slices with a radius of 20 mm and a uniform thickness of 1.5 mm. These skin samples were mounted in Franz diffusion cells, in which the stratum corneum faced the donor chamber, which was filled with methotrexate-loaded hydrogel, while the receiving chamber was filled with PBS solution. The control group was treated with MTX-PBS solution. To prevent water evaporation, the Franz diffusion cell was sealed with plastic film and kept at a temperature of 37°C with continuous shaking for 24 hours. At predetermined intervals, 2 mL of solution was withdrawn from the receptor compartment and supplemented with an equal amount of fresh receptor solution to maintain a consistent volume. The cumulative release rate and permeation rate of MTX through the skin were calculated using the following formula:
[0055]
[0056] In the formula, Q n represents the cumulative percentage of MTX penetration into the skin, V represents the volume of the culture medium (10 mL), C n and C are the concentrations of MTX in the culture medium at time points n and (n-1), respectively. iis the volume of medium removed at different time points (2 mL), and A is the total amount of MTX applied to the skin.
[0057] 7. The therapeutic effect of MTX-SBC / CS hydrogel on psoriasis
[0058] C57BL / 6 mice were randomly divided into 5 groups (n=5 in each group), and the dorsal skin of the mice was shaved 48 hours before topical treatment. One group served as a healthy control, and the other four groups were all treated with 62.5 mg of 5% imiquimod (IMQ) cream on the dorsal skin for 5 consecutive days to induce psoriatic dermatitis. After using IMQ, the mice were treated with SBC / CS gel (1 mL), MTX-SBC / CS gel (1 mL) and betamethasone cream every other day for a total of 3 times. The severity of skin inflammation was assessed daily using the Psoriasis Severity Index (PASI) scoring system, which includes three indicators: erythema, scaling and skin thickness. Each group was scored from 0 to 4 (0=none; 1=mild; 2=moderate; 3=severe; 4=very severe). After the modeling was completed, the skin of the psoriasis modeling site was dissected for H&E staining. Total RNA was extracted from the skin samples using Trizol. The mRNA expression levels of IL-17, IFN-γ, TNF-α, and S100A8 were evaluated by qPCR.
[0059] Example 2
[0060] Synthesis of SBC / CS hydrogel
[0061] 1g of chitosan was dissolved in 50ml of 2% acetic acid solution to prepare a 2% chitosan acetic acid solution. 5ml of 2% chitosan acetic acid solution or 20ml of 2% chitosan acetic acid solution was added to 10ml of sulfonated bacterial cellulose suspension, and the mixture was placed at room temperature for 12 hours to prepare SBC / CS hydrogel. The SBC / CS hydrogel prepared under this condition had an appropriate initial water content and exhibited high mechanical properties.
[0062] Comparative Example 1
[0063] This comparative example is substantially the same as Example 1, except that the mass ratios of chitosan and sulfonated bacterial cellulose are 10:1 and 1:0.5, respectively. The initial water content of the hydrogel prepared under this condition is higher than that of Example 1, and the mechanical properties of the hydrogel are reduced due to the excessively high initial water content.
[0064] Figure 1 Schematic diagram of the preparation of sulfonated bacterial cellulose / chitosan hydrogel loaded with methotrexate.
[0065] Figure 2The molecular dynamics simulation diagram of MTX adsorption on BC and SBC. Compared with the original BC polymer (BCm12), the sulfated BC polymer (BCm12S6) has a stronger MTX adsorption capacity. After 20ns, BCm12 adsorbed 1 MTX molecule, while BCm12S6 adsorbed 4. The average number of hydrogen bonds formed between BCm12S6 / MTX was significantly higher than that of BCm12 / MTX. The van der Waals force (vdW) and Coulomb force (Coul) between BCm12 and MTX were -28.69 kJ / mol and -17.62 kJ / mol, respectively, while the interaction force between BCm12S6 and MTX increased to -97.98 kJ / mol (vdW) and -56.61 kJ / mol (Coul), respectively, confirming the higher drug loading potential of SBC compared with BC.
[0066] Figure 3 The SEM images of SBC, SBC / CS hydrogel, and MTX-SBC / CS hydrogel show that SBC combines with CS through a hydrogen bond network to eventually form a three-dimensional porous matrix. In contrast, MTX-SBC / CS hydrogel has a more obvious lamellar structure, which is mainly attributed to the drug molecules occupying the inherent pores. This lamellar structure retains the relatively porous nature, which promotes the release of MTX under further application conditions.
[0067] Figure 4 FTIR detection diagrams of SBC, CS, MTX, SBC / CS hydrogel, and MTX-SBC / CS hydrogel. FTIR analysis showed that SBC / CS hydrogel exhibited several characteristic absorption peaks, especially at 1051 cm -1 and 804cm -1 MTX at 3356cm -1 、1645cm -1 and 1229cm -1 Absorption bands appeared at , corresponding to OH stretching vibration, C=O stretching vibration and CN stretching vibration. The most characteristic peaks of MTX existed in the spectrum of MTX-SBC / CS hydrogel, confirming the encapsulation process.
[0068] Figure 5 The bioadhesive properties of the hydrogel were evaluated. It can be seen that the MTX-SBC / CS hydrogel adheres firmly to the surface of pig skin and shows resilience to deformation caused by stretching, twisting, bending or immersion in water. This behavior indicates that the hydrogel has sufficient tissue bonding strength to withstand the frequent movements encountered in the human body. The quantitative adhesion properties of the hydrogel were determined by lap shear testing, and the adhesion strength was approximately 2.78±0.09kPa. At the same time, the gel is able to adhere tightly to a variety of materials, including glass, metal, rubber, magnets and plastics.
[0069] Figure 6 Skin irritation studies were performed to evaluate the sensitization potential of MTX, SBC / CS hydrogel, and MTX-SBC / CS hydrogel. Compared with the DNCB group, SBC / CS hydrogel and MTX-SBC / CS hydrogel showed no significant skin irritation, indicating a lower sensitization potential.
[0070] Figure 7 The peak concentrations of MTX in CS solution, PBS, and SBC solution were shown to be 0.91±0.08, 1.78±0.02, and 9.87±0.71 mg / mL, respectively, and MTX exhibited the greatest solubility in SBC solution. Free methotrexate showed rapid dispersion, reaching approximately 60% release within the first 4 h. In contrast, SBC / CS hydrogels promoted a more controlled and sustained release profile, with a cumulative dispersion of approximately 60% within 24 h. At an acidic pH of 5.5, the release rates of both free MTX and encapsulated MTX in MTX-SBC / CS hydrogels decreased, reaching 60% and 35% release rates within 24 h, respectively. Therefore, MTX-SBC / CS gels have enhanced MTX solubility and sustained release properties, and the slightly acidic conditions of the skin may enhance the gradual release of methotrexate.
[0071] Figure 8 This is an in vitro skin permeability study. In a mouse model, FITC was used to replace methotrexate to evaluate the penetration effect of SBC / CS hydrogel. The experiment observed that only a weak fluorescence signal was detected on the mouse skin surface in the FITC-PBS solution group 24 hours after administration. The FITC-labeled SBC / CS hydrogel showed a significant penetration effect, which was able to smoothly penetrate the stratum corneum of the skin and enter the epidermis, and the strong fluorescence of FITC was clearly recorded. At the same time, the MTX penetration-promoting effect of SBC / CS hydrogel was evaluated in vitro, using pig skin as a model. By comparing the drug permeability of MTX-SBC / CS hydrogel and MTX-PBS solution within 24 hours, the results showed that the permeability of MTX-SBC / CS hydrogel reached 52.7%, which was significantly higher than the 31.8% of MTX-PBS solution. This result shows that MTX-SBC / CS hydrogel can increase the penetration efficiency of MTX by about 1.7 times.
[0072] Fig. 9 Compared with the control group, the application of MTX-SBC / CS hydrogel can significantly improve IMQ-induced erythema, desquamation, skin thickening, etc. The PASI score showed that the inflammatory response in the MTX-SBC / CS hydrogel treatment group was significantly reduced.
[0073] Fig.10Histopathology showed that untreated mice exhibited psoriasis-related features, including acanthosis, increased angiogenesis, and keratinocyte proliferation. In contrast, the relevant features of the MTX-SBC / CS hydrogel group were significantly weakened, and the measurement of epidermal thickness also showed a significant reduction in the treatment group, which is consistent with the therapeutic effect of betamethasone, but MTX can avoid the adverse reactions such as skin atrophy and capillary dilation caused by long-term use of hormone ointments such as betamethasone. qRT-PCR detection showed that MTX-SBC / CS hydrogel treatment significantly reduced IL-17, IFN-γ, TNF-α, and S100A8 mRNA levels. And the use of SBC / CS hydrogel alone also showed a decrease in cytokine levels, indicating that it has inherent anti-inflammatory activity.
Claims
1. A method for preparing a sulfonated bacterial cellulose / chitosan hydrogel loaded with methotrexate for the treatment of psoriasis, characterized in that: The following steps are involved: Step 1, dissolving bacterial cellulose and aminosulfonic acid in DMF, reacting in a sealed container at 50±10° C. for 2-12 hours, adding anhydrous ethanol to terminate the reaction, adjusting the pH to 7-8, dialyzing, washing, centrifuging and homogenizing to obtain a sulfonated bacterial cellulose suspension; Step 2, mixing methotrexate with the sulfonated bacterial cellulose suspension, stirring evenly, to obtain a sulfonated bacterial cellulose suspension loaded with methotrexate; Step 3, according to the mass ratio of chitosan to sulfonated bacterial cellulose of 1:4 to 1:1, the sulfonated bacterial cellulose suspension loaded with methotrexate and the acetic acid solution of chitosan are mixed, stirred evenly, and allowed to stand and solidify to obtain the sulfonated bacterial cellulose / chitosan hydrogel loaded with methotrexate.
2. The preparation method according to claim 1, characterized in that: In step 1, the mass ratio of bacterial cellulose to aminosulfonic acid is 2:7.5, and the reaction time is 4 to 8 hours; in the sulfonated bacterial cellulose suspension, the concentration of sulfonated bacterial cellulose is 0.04 g / ml; the molecular weight of the dialysis bag used for dialysis is 8000 to 14000, and the dialysis time is 5 to 7 days.
3. The preparation method according to claim 1, characterized in that: In step 2, the mass ratio of methotrexate to sulfonated bacterial cellulose is 1:4, and the concentration of methotrexate in the sulfonated bacterial cellulose suspension loaded with methotrexate is 1 mg / ml.
4. The preparation method according to claim 1, characterized in that: In step 2, the stirring method is magnetic stirring, the stirring time is 30 minutes, and the rotation speed is 100 rpm.
5. The preparation method according to claim 1, characterized in that: In step 3, the acetic acid solution of chitosan is prepared by dissolving chitosan in a 2% (w / v) acetic acid solution, and the concentration of chitosan is 1-2% (w / v).
6. The preparation method according to claim 1, characterized in that: In step 3, the mass ratio of chitosan to sulfonated bacterial cellulose is 1:
2.
7. The preparation method according to claim 1, characterized in that: In step 3, the standing temperature is room temperature and the standing time is 12 hours.
8. The methotrexate-loaded sulfonated bacterial cellulose / chitosan hydrogel prepared according to the preparation method described in any one of claims 1 to 7.
9. Use of the methotrexate-loaded sulfonated bacterial cellulose / chitosan hydrogel according to claim 8 in the preparation of a drug for treating psoriasis.
Citation Information
Cited By
Bacterial cellulose injectable gel and preparation method thereof
CN120459372A
A bacterial cellulose injectable gel and a method for its preparation
CN120459372B
Biomass-based tea tree essential oil slow-release application patch for treating psoriasis and preparation method thereof
CN121371264A